Mutations in the nuclear bile acid receptor FXR cause progressive familial intrahepatic cholestasis - Natalia Gomez-Ospina (Nature Portfolio, 2016)
Neonatal cholestasis is a result of elevated bile acid levels, and is associated with mutations in genes regulating bile acid homeostasis. Here the authors identify mutations in the bile acid sensing farnesoid X receptor in four individuals with neonatal cholestasis from two unrelated families.